1998
DOI: 10.1016/s0925-4773(98)00112-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression patterns of Wnt genes in the murine female reproductive tract during development and the estrous cycle

Abstract: The murine female reproductive tract differentiates during postnatal development. This process of cytodifferentiation and morphogenesis is dependent upon specific mesenchymal-epithelial interactions as well as circulating steroid hormones (Cunha, G.R., 1976. Int. Rev. Cytol. 47, 137-194; Pavlova, A. et al., 1994. Development 120, 335-346). Members of the Wnt family of signaling molecules have been recently identified in this system (Pavlova, A. et al., 1994. Development 120, 335-346; Bui, T.D. et al., 1997. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
1
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 29 publications
4
117
1
5
Order By: Relevance
“…Since SFRP-2 negatively regulates Wnt functions, it is envisioned that its down-regulation by estrogen allows Wnt-frizzled signaling to execute specific uterine functions. Wnt ligands participate in mesenchymal-epithelial interactions (66), and uterine expression of Wnt ligands (Wnt-4, Wnt-5a, and Wnt-7) is tightly regulated during the estrous cycle by estrogen and/or P 4 (67,68). Since Wnts regulate cellular proliferation, differentiation, and/or reorganization, we suggest that they act as estrogen-mediated transducers of these events in the uterus.…”
Section: Fig 8 Effects Of P 4 On Estrogen-induced Uterine Expressiomentioning
confidence: 87%
“…Since SFRP-2 negatively regulates Wnt functions, it is envisioned that its down-regulation by estrogen allows Wnt-frizzled signaling to execute specific uterine functions. Wnt ligands participate in mesenchymal-epithelial interactions (66), and uterine expression of Wnt ligands (Wnt-4, Wnt-5a, and Wnt-7) is tightly regulated during the estrous cycle by estrogen and/or P 4 (67,68). Since Wnts regulate cellular proliferation, differentiation, and/or reorganization, we suggest that they act as estrogen-mediated transducers of these events in the uterus.…”
Section: Fig 8 Effects Of P 4 On Estrogen-induced Uterine Expressiomentioning
confidence: 87%
“…Noncanonical WNT signaling encompasses a variety of signaling pathways that involve different WNT receptors (i.e., ROR2 and RYK) and mediators (i.e., calcium, MAPK8/9/10, and CAMK2) that regulate cell migration and movement. A subset of Wnts (Wnt4, Wnt5a, and Wnt7a) is involved in müllerian duct patterning and differentiation during development of the female reproductive tract in the embryo [14,19,20]. Postnatal uterine morphogenesis also involves a number of different Wnts and their signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In the endometrium, Wnt7a functions in cell-cell communication and is responsive to changes in levels of sex steroid hormones [19]. Our lab has found that Wnt7a interacts with Fzd5 to activate β-catenin/canonical signaling and induce proliferation in endometrial cancer cells [Carmon and Loose, unpublished].…”
mentioning
confidence: 99%